Plummer Vinson syndrome in a male and his chromosomal study – A case report - Santosh K. Swain; Rajalaxmi Panigrahy; Mahesh C. Sahu (Egyptian Journal of Medical Human Genetics, 2015)
Plummer Vinson syndrome (PVS) is a triad of iron deficiency anemia, esophageal web and dysphagia. The exact etiology of PVS remains controversial but it has been associated with nutritional deficiency, autoimmune disorders, hereditary factors and remarkable high female predominance. This paper reports an atypical presentation of PVS in a 38 year old Indian male with special emphasis given on chromosomal analysis. Chromosomal assessment is done as it is a good predictor of the possibility of development of post-cricoid carcinoma (PCC) in patients with PVS. Chromosomal aberrations like translocation, gain, loss, breakpoints and duplications are studied and they revealed normal male chromosomal pairing.